(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The research aims to clarify the importance of adoption of International Accounting Standard No. (12) "Income Taxes" as a tool for the measurement and disclosure of income taxes in the financial statements، and how to deal with the differences that arise as a result of difference in net profit accounting for net tax profit ،The problem of the research focused on the disparity between the income tax estimate in Iraq in accordance with the accounting standards and financial reporting and assessment of income tax in accordance with the tax laws and legislation, this discrepancy has led to the emergence of differences between accounting profit and tax profit (temporary differences and permanent differences) and these differences of which affect the estimate tax in subsequent years, a temporary differences but the differences, the study has shown that the process of the Iraqi Investment Bank deferred tax liabilities arising from temporary differences by (313 833 600) for the years (2011).The research has concluded a set of conclusions, including that set off the tax assets and liabilities as permitted by the standard underconsideration was compatible with the principle of revenue expenses interview, in addition to a set of recommendations which included the need to amend the tax Iraqi law and make it compatible with international and local standards requirement